2018
DOI: 10.1002/jum.14754
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of subclinical atherosclerosis using ultrasound radiofrequency data technology in patients diagnosed with ankylosing spondylitis

Abstract: Subclinical atherosclerosis is not accelerated in AS patients with low disease activity, although insufficiently controlled disease activity may result in increased carotid IMT and atheromatosis. Radiofrequency data technology provides a noninvasive method for accurately and quantitatively demonstrating CCA-IMT elevation and the decrease in vascular elasticity in patients with AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Our cIMT results, comparing patients with r-axSpA with controls, agree with findings presented previously [11,[18][19][20][21] but conflict with others [22][23][24][25]. However, in a recent systematic review and meta-analysis by Yuan et al [11], the authors concluded that the majority of current literature on this topic finds that cIMT is significantly increased in patients with r-axSpA compared to controls.…”
Section: Discussionsupporting
confidence: 79%
“…Our cIMT results, comparing patients with r-axSpA with controls, agree with findings presented previously [11,[18][19][20][21] but conflict with others [22][23][24][25]. However, in a recent systematic review and meta-analysis by Yuan et al [11], the authors concluded that the majority of current literature on this topic finds that cIMT is significantly increased in patients with r-axSpA compared to controls.…”
Section: Discussionsupporting
confidence: 79%